2020
DOI: 10.4269/ajtmh.19-0428
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Morbidity, Physical Fitness, and Perceived Quality of Life among Schoolchildren following Four Years of Different Mass Drug Administration Strategies against Schistosoma mansoni Infection in Mwanza Region, Northwestern Tanzania

Abstract: Schistosoma mansoni infection negatively impacts children's physical health and may influence general well-being. Schistosomiasis control programs aim at reducing morbidity through mass drug administration (MDA). This study aimed to compare morbidity markers between two cohorts of Tanzanian schoolchildren with initial high prevalence of S. mansoni infection. One cohort (N = 254 at baseline) received annual MDA for 4 years using community-wide treatment (CWT). The second cohort (N = 318 at baseline) received sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Assessment of HRQOL in schistosomiasis patients is commonly used to evaluate therapeutic interventions and mass drug administration strategies in endemic areas (16,19,21,(23)(24)(25). However, studies that determine the burden of severe forms of schistosomiasis on patients' quality of life are scarce and rarely include an appropriate control group with similar sociodemographic background for comparison (15,17,18,22,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of HRQOL in schistosomiasis patients is commonly used to evaluate therapeutic interventions and mass drug administration strategies in endemic areas (16,19,21,(23)(24)(25). However, studies that determine the burden of severe forms of schistosomiasis on patients' quality of life are scarce and rarely include an appropriate control group with similar sociodemographic background for comparison (15,17,18,22,26).…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of HRQOL, together with morbidity and mortality measurements, is crucial to determine the disease's burden in the community, evaluate interventions and standard health care policies, and identify areas that require further improvement (12-16). Generic HRQOL, such as WHOQOL-BREF or EQ-5D-3L, has been validated in different languages, cultural settings, and different diseases, including schistosomiasis (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…The Kenya and Tanzania gaining control studies were able to successfully complete their Year 3 and Year 5 cohort reexaminations. 41 43 In a secondary analysis of their pooled S. mansoni longitudinal data, overall infection intensity and odds of infection were significantly reduced in both treatment arms of the study. 44 Furthermore, both annual CWT and every-other-year SBT were associated with reduced odds of undernutrition in Year 5 (at the time, the children were aged 12–13 years).…”
Section: Schistosomiasis Consortium For Operational Research Longitudmentioning
confidence: 99%
“…The effect of severe and chronic S. mansoni infection has been associated with increased morbidity and reduced HRQoL [16,17]. However, short-term effects of mild infections on HRQoL have yielded contradictory results: some studies showed negative associations among adults and children, with higher impact on emotional rather than physical dimensions [18][19][20], but others reported no associations [21][22][23]. Importantly, the effect of MDA on morbidity outcomes and HRQoL remains unclear [20,21,24].…”
Section: Introductionmentioning
confidence: 99%